2014
DOI: 10.5812/archneurosci.18555
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Striatal Dopamine and Hippocampal Serotonin Following Induction of Anxiety/Depressive-Like Behaviors by Bisphenol A

Abstract: Background: Anxiety and depression are common nonmotor symptoms of Parkinson's disease (PD). Objectives: We investigated whether Bisphenol A (BPA) is capable of inducing anxiety/depressive-like behaviors and neurotransmitter alterations that are similar to those observed in PD. Materials and Methods:To test this hypothesis, we used a zebrafish animal model and conducted behavioral and histological assays. Results: BPA produced anxiety/depression-like behavioral signs for 14 days following administration. Alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In mammals, depletion of 5-HT level in rat brain induces anxiety ( 93 ) and acute reduction of tryptophan increases the anxiety level in patients of a social anxiety disorder ( 94 ). The role of 5-HT in anxiety is also reported in zebrafish ( 20 , 95 ). Buspirone, partial agonist for 5-HT1A receptor, exerts anxiolytic-like effect in zebrafish ( 96 ).…”
Section: Discussionmentioning
confidence: 82%
“…In mammals, depletion of 5-HT level in rat brain induces anxiety ( 93 ) and acute reduction of tryptophan increases the anxiety level in patients of a social anxiety disorder ( 94 ). The role of 5-HT in anxiety is also reported in zebrafish ( 20 , 95 ). Buspirone, partial agonist for 5-HT1A receptor, exerts anxiolytic-like effect in zebrafish ( 96 ).…”
Section: Discussionmentioning
confidence: 82%
“…Different studies have shown that 5-HT concentration when increased in the brain also increases anxiety and a reduction of 5-HT level reduces anxiety. 104,105 Serotonergic neurons are involved in the alteration of appetite, energy, sleep, mood and cognitive function in anxiety. Its role in anxiety is supported by its modulating effect on the locus coeruleus and its projections to the amygdale.…”
Section: Fig 2: Showing Role Of Different Neurotransmitters In Anxietymentioning
confidence: 99%
“…Numerous neurotransmitters are implicated in the neurobiological controlling of anxiety (Mendes et al 2017 ; Pałasz et al 2021 ). Serotonin and dopamine signaling is shown to be positively involved in the pathogenesis of anxiety (Akimova et al 2009 ; Jia & Pittman 2015 ; Murphy et al 2013 ). In the current experiment, ZNPs-exposed rats displayed a significant increase in serotonin and dopamine brain content.…”
Section: Discussionmentioning
confidence: 99%